High Performance Liquid Chromatographic Determination of Etoricoxib in Human Plasma - K. SHAKYA, ASHOK; A. KHALAF, NOOMAN (Asian Journal of Chemistry, 2010)
A simple, sensitive and reproducible high performance liquid chromatographic (HPLC) has been developed for the analysis of etoricoxib in plasma. This validated method is successfully applied for the estimation of etoricoxib in human volunteers. The HPLC analysis was performed using BDS-Hypersil C-18 (250 mm × 4.6 mm, 5 μm, Thermo electron corporation, USA) column. The mobile phase used was aqueous buffer (containing 0.3 mL triethyl amine (as peak modifier) and 0.4 mL orthophosphoric acid per liter) : acetonitrile (62:38, v/v). The analytes were detected at 284 nm. The total time for a chromatographic separation was ca. 10 min. Extraction of etoricoxib from plasma was carried out using diethylether:dichloromethane (6:4; v/v). The validated quantitation ranges of this method were 15-3200 ng/mL with coefficients of variation of 2.2-5.4 %. In between and within batch precision was 1.3-5.6 and 0.8-6.7 %, respectively. In between and within batch relative error was 0.6-(-4.8) and 0.9-4.7 %, respectively. Stability of etoricoxib in plasma was > 89 %, with no evidence of degradation during sample processing and 45 days storage in a deep freezer at -70ºC. This validated method is sensitive and simple with precision of < 6 % and can be used for pharmacokinetic studies and therapeutic drug monitoring.